2021
DOI: 10.1186/s41938-021-00447-w
|View full text |Cite
|
Sign up to set email alerts
|

Virulence of Beauveria bassiana and Metarhizium anisopliae on different stages of the pink bollworm, Pectinophora gossypiella (Saunders) (Lepidoptera: Gelechiidae)

Abstract: Background The pink bollworm, Pectinophora gossypiella, is the most destructive pests of the cotton plant in Egypt. Due to the several problems of insecticides, the present study was conducted to evaluate the toxicity effect of the entomopathogenic fungi (EPF), Beauveria bassiana and Metarhizium anisopliae, against the different stages of the pink bollworm, Pectinophora gossypiella (Saunders) (Lepidoptera: Gelechiidae) Results The fungal isolates e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 16 publications
1
1
0
Order By: Relevance
“…The results of the current study show that B. bassiana PfBb, a strain collected from P. flammans larvae, had strong virulence to first to third instar larvae of S. frugiperda, though its pathogenicity gradually decreased with the increase of the larval instars ( Figure 2 and Figure 3 ; Table 1 and Table 2 ). Similar results have also been reported when pathogenic fungi are collected from other host species [ 35 ] or when other pest insects are infected with B. bassiana [ 46 , 47 ]. For example, the application of B. bassiana has a higher effect on the young larvae of Indarbela dea [ 48 ], suggesting younger larvae are more susceptible to B. bassiana than older larvae [ 49 ].…”
Section: Discussionsupporting
confidence: 86%
“…The results of the current study show that B. bassiana PfBb, a strain collected from P. flammans larvae, had strong virulence to first to third instar larvae of S. frugiperda, though its pathogenicity gradually decreased with the increase of the larval instars ( Figure 2 and Figure 3 ; Table 1 and Table 2 ). Similar results have also been reported when pathogenic fungi are collected from other host species [ 35 ] or when other pest insects are infected with B. bassiana [ 46 , 47 ]. For example, the application of B. bassiana has a higher effect on the young larvae of Indarbela dea [ 48 ], suggesting younger larvae are more susceptible to B. bassiana than older larvae [ 49 ].…”
Section: Discussionsupporting
confidence: 86%
“…Similarly, entomopathogenic fungi demonstrated effectiveness in causing mortality across various developmental stages of P. gossypiella and B. bassiana exhibited greater toxicity induction compared to M. anisopliae (Omar et al, 2021) under laboratory bioassay studies. Compatibility studies also showed the highest mortality rates when combining V. lecanii, M. anisopliae and B. bassiana with A. indica extract.…”
mentioning
confidence: 95%
“…Similarly, entomopathogenic fungi demonstrated effectiveness in causing mortality across various developmental stages of P. gossypiella and B. bassiana exhibited greater toxicity induction compared to M. anisopliae (Omar et al, 2021) under laboratory bioassay studies. Compatibility studies also showed the highest mortality rates when combining V. lecanii, M. anisopliae and B. bassiana with A. indica extract.…”
mentioning
confidence: 95%